EKSPLORASI MOTIVASI MAHASISWA: FAKTOR-FAKTOR YANG MEMBENTUK KEPUTUSAN MEMILIH PROGRAM STUDI PARIWISATA FAKULTAS DESAIN HUKUM DAN PARIWISATA IIB DARMAJAYA - Lefiani, Nia (Jurnal Pariwisata PaRAMA : Panorama, Recreation, Accomodation, Merchandise, Accessbility, 2025)
Tourism is one of the leading industries proliferating in the world today. This increase has the potential to reduce the unemployment rate. The purpose of this research is to create a SWOT analysis to determine the strengths and weaknesses of the Tourism Study Program as well as take advantage of marketing opportunities and overcome threats to the Higher Education business environment. Identify the dominant factors that make students interested in enrolling in the Tourism Study Program. Combining the results of SWOT analysis and factor analysis to develop a holistic marketing strategy for the Tourism Study Program. The method in this research uses the EFAS (External Factors Analysis Summary) and IFAS (Internal Factors Analysis Summary) matrices. The test tool in this research is the Cochran Q Test. The results of data processing can conclude that 5 attributes form factors of prospective students' interest in the Tourism Study Program. Namely, Ease of getting a job, Learn Digital Tourism Applications, In line with tourism developments, Deepening tourism knowledge, and Combination of gastronomy, management, and technology. Based on the results of this factor analysis, the Marketing Bureau at IIB Darmajaya can design a marketing campaign that focuses on the 5 attributes that have been identified. Apart from that, the strengths, weaknesses, opportunities, and threats of the Tourism Study Program have also been identified while maintaining the quality of the curriculum, human resources, and infrastructure in line with current developments.